A study of infraorbital nerve swelling associated with immunoglobulin G4 Mikulicz's disease. Issue 5 (September 2014) - Takano, Kenichi; Yajima, Ryoto; Seki, Nobuhiko; Abe, Ayumi; Yamamoto, Motohisa; Takahashi, Hiroki; Himi, Tetsuo
Abstract Objectives. Recent studies revealed that Mikulicz's disease (MD) should be considered as an immunoglobulin (Ig) G4-related disease with aspects of systemic disorders involving the orbit. This study aimed to analyze the relationship between Immunoglobulin G4 (IgG4)-related MD and infraorbital nerve thickness. Methods. We measured infraorbital nerve thickness in 68 patients diagnosed as IgG4-related MD at our hospital and performed computed tomography scans of the head and neck region before treatment and compared these scans with those of the control group. Results. The mean infraorbital nerve diameter (± standard deviation) was 3.2 ± 1.2 mm in patients with IgG4-related MD, and 2.6 ± 0.3 mm in the control group. Infraorbital nerves were significantly thicker in patients with IgG4-related MD. Nerve swelling was found in 20 of 68 patients (29.4%) with a cutoff value of 3.3 mm because this value was obtained from diameter of nerves in the control group + 2 standard deviation mm. No patients in the control group showed nerve swelling. In addition, we found significant correlations between infraorbital nerve swelling and serum IgG4 levels as well as the existence of multiple organ lesions. Conclusions. We found that significant infraorbital nerve swelling occurred in patients with IgG4-related MD and was thought to be a part of IgG4-related disease.